GAMBARAN TINGKAT DEPRESI PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RSUD DR. SOEDARSO PONTIANAK TAHUN 2012 - ., Rustina (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Chronic renal failure (CRF) occurs after the damage ofnephron mass and losses its ability to perform regulatory and excretoryfunctions and must undergo hemodialysis (HD) to preserve life. Theimpact of illness and treatment procedures are the stressor that can causedepression.Objective. The objective of this research was to describe the level ofdepression in patients with CRF on HD treatment in RSUD dr. SoedarsoPontianak.Method. The method used for the research was descriptive survey study.The subjects of this study were 67 patients with CRF on HD treatment inRSUD dr. Soedarso on July 2012. Sample taken by consecutive sampling.The qualified sample was interviewed with Beck Depression Inventory II(BDI II) for determining the level of depression.Result. The result shows that the prevalence of depression in patientswith CRF on HD treatment is 35,82%. In details, mild depression is28,36%, moderate depression 4,48%, and severe depression is 2,98%.Conclusion. Majority of the depression level in patients with CRF on HDtreatment in RSUD dr.Soedarso year 2012 is mild depression and thedominant characteristics in respondent with depression are: age 51-56,male, married, senior high school graduated, and housewives.Keywords: Chronic Renal Failure (CRF), Hemodialysis (HD), depression,Beck Depression Inventory II (BDI II)